2016
DOI: 10.18632/oncotarget.7820
|View full text |Cite
|
Sign up to set email alerts
|

Nitrilase 1 modulates lung tumor progression in vitro and in vivo

Abstract: Uncovering novel growth modulators for non-small cell lung cancer (NSCLC) may lead to new therapies for these patients. Previous studies suggest Nit1 suppresses chemically induced carcinogenesis of the foregut in a mouse model. In this study we aimed to determine the role of Nit1 in a transgenic mouse lung cancer model driven by a G12D Kras mutation. Nit1 knockout mice (Nit1−/−) were crossed with KrasG12D/+ mice to investigate whether a G12D Kras mutation and Nit1 inactivation interact to promote or inhibit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Noncontrast whole-body CT imaging of 4-to 6-month-old mice without respiratory or cardiac gating was performed using the MicroCAT II small-animal CT scanner (Siemens ImTek Inc.) at 80 kVp and 500 mA (25). The DICOM data were imported to the MIM6.5 (MIM Software Inc.) for tumor contouring and 3D reconstruction with different colors using the combination of manual segmentation and semiautomated contouring methods (26). These analyses were consistent between two independent operators and performed in a blinded manner.…”
Section: Characterization Of Mouse Lung Cancermentioning
confidence: 99%
“…Noncontrast whole-body CT imaging of 4-to 6-month-old mice without respiratory or cardiac gating was performed using the MicroCAT II small-animal CT scanner (Siemens ImTek Inc.) at 80 kVp and 500 mA (25). The DICOM data were imported to the MIM6.5 (MIM Software Inc.) for tumor contouring and 3D reconstruction with different colors using the combination of manual segmentation and semiautomated contouring methods (26). These analyses were consistent between two independent operators and performed in a blinded manner.…”
Section: Characterization Of Mouse Lung Cancermentioning
confidence: 99%
“…However, we do not see any obvious connection between the enzymic functions of Fhit and of Nit1. We must also stress that, although data collected in mammalian cells, mice models, and human samples suggest that Nit1 promotes apoptosis (23) and affects, in a complex fashion, the development and progression of some types of tumors (23,43), it is uncertain whether these roles bear any connection with the enzyme's catalytic function. In fact, mutation of the conserved active site cysteine to an alanine did not alter the ability of Nit1 to promote apoptosis in human cells (23).…”
Section: Nit1 Is Useful To Correct the Unspecific Activity Of Transammentioning
confidence: 99%
“…The deficiency of NIT1 led to an increase in the incidence of N -nitrosomethylbenzylamine-induced murine gastric cancer 23 . However, a recent study has shown that NIT1 was overexpressed in human lung cancer tissues compared with that in non-malignant lung tissues and accelerated lung tumour progression in vitro and in vivo 31 . This inconsistent result may be due to the heterogeneity of the tumours.…”
Section: Discussionmentioning
confidence: 99%